1994
DOI: 10.1086/117245
|View full text |Cite
|
Sign up to set email alerts
|

Chaotic motion in the outer asteroid belt and its relation to the age of the solar system

Abstract: Recently, we analyzed a relation, found for chaotic orbits, between the Lyapunov time T L (the inverse of the maximum Lyapunov exponent) and the "event" time T e (the time at which an orbit becomes clearly unstable). In this paper we treat two new problems. First, we apply this T L-T e relation to numerical integrations of 25 outer-belt asteroids and show that, when viewed in the proper context of a Gaussian distribution of event time residuals, none of the 25 objects exhibits an anomalously short Lyapunov tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 18 publications
1
36
1
Order By: Relevance
“…The time required for that to happen is called the "event time" (T E ). Several studies involving the instability of asteroids disturbed by Jupiter and/or other planets (Soper et al 1990; Lecar et al 1992;Franklin et al 1993;Levison & Duncan 1993;Murison et al 1994;Whipple 1995) have claimed that there is a simple relation between the Lyapunov time, T L , and the event time, T E (to become a Jupiter's crosser, for example) given by…”
Section: Introductionmentioning
confidence: 99%
“…The time required for that to happen is called the "event time" (T E ). Several studies involving the instability of asteroids disturbed by Jupiter and/or other planets (Soper et al 1990; Lecar et al 1992;Franklin et al 1993;Levison & Duncan 1993;Murison et al 1994;Whipple 1995) have claimed that there is a simple relation between the Lyapunov time, T L , and the event time, T E (to become a Jupiter's crosser, for example) given by…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, we have a substantially better fit. be regarded as "laws" in the sense of Murison, Lecar & Franklin (1994). Furthermore, due to their statistical nature, they cannot be used for any particular object, only for populations.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Because the motion is close to a separatrix (or takes place within it), it can be influenced by the stickiness phenomenon. This effect was studied, e.g., by Murison et al (1994), and recently, by Tsiganis et al (2000Tsiganis et al ( , 2002, for the models of asteroid motion in the Solar system. The former authors found that the long-term evolution of chaotic orbits initiated in the vicinity of some high-order mean motion resonances with Jupiter is possible if there exist no resonant periodic orbits in the framework of the elliptic-three body problem.…”
Section: Analysis Of the Initial Conditionmentioning
confidence: 98%